2021
DOI: 10.3390/ijms22010454
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Provides New Insights into the Molecular Events Involved in “Ball-Skin versus Bladder Effect” on Fruit Cracking in Litchi

Abstract: Fruit cracking is a disorder of fruit development in response to internal or external cues, which causes a loss in the economic value of fruit. Therefore, exploring the mechanism underlying fruit cracking is of great significance to increase the economic yield of fruit trees. However, the molecular mechanism underlying fruit cracking is still poorly understood. Litchi, as an important tropical and subtropical fruit crop, contributes significantly to the gross agricultural product in Southeast Asia. One importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 58 publications
(66 reference statements)
2
23
0
3
Order By: Relevance
“…Our co-expression analysis detected a strong correlation between hormone metabolism and other cracking-related metabolic activities. Consistent with the findings of previous studies on atemoya [ 10 ] and lychee [ 12 , 47 ], we observed that the upregulated expression of ABA-related and IAA-related DEGs in cracking jujube fruits can lead to increased ABA and IAA levels in fruits, which might promote fruit cracking directly or indirectly by upregulating the expression of specific TFs, such as MYB , WRKY , and NAC , to increase growth-related gene expression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our co-expression analysis detected a strong correlation between hormone metabolism and other cracking-related metabolic activities. Consistent with the findings of previous studies on atemoya [ 10 ] and lychee [ 12 , 47 ], we observed that the upregulated expression of ABA-related and IAA-related DEGs in cracking jujube fruits can lead to increased ABA and IAA levels in fruits, which might promote fruit cracking directly or indirectly by upregulating the expression of specific TFs, such as MYB , WRKY , and NAC , to increase growth-related gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…In another study involving A. thaliana , the expression of the sheepgrass LcMYB4 gene positively regulated the accumulation of soluble sugars in transgenic plants [ 55 ]. Transcription factors regulate plant growth and development by modulating the transcription of specific target genes [ 12 ]. In our study, we revealed a positive correlation between TFs and fruit cracking-related processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit development is a complex biological process that involves nutrient formation and secondary product metabolism, directly affecting fruit quality formation and commodity value [59]. Previous studies have found that the development, maturation, senescence and quality formation of fruits are specifically regulated by many environmental and regulatory factors, especially NAC TFs [38].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors are closely related to plant development and responses to the environment [ 36 ]. During the development of male gametes in Arabidopsis thaliana , more than 600 transcription factors interact with each other to form a dynamic regulatory network [ 37 ].…”
Section: Discussionmentioning
confidence: 99%